Transforming nursing education to support health workforce and nursing education development in Angola: An integrative review - Mário Fresta; Inês Fronteira; Judith Luacute; Paulo Ferrinho (Elsevier, 2023)
The Angolan State has been looking for a way to strengthen the health sector with a balanced workforce for which nursing is a cornerstone. This study reviews the evolution of nursing education in Angola, in order to better understand the contribution of the educational sector to nursing workforce development. Methods: Integrative review of unpublished and published documents and literature on nursing education in Angola. The literature is qualitatively analyzed and discussed using the policy triangle framework proposed by Walt and Gilson. Results and discussion: The transformation of the nursing workforce in Angola has gone through four phases: (i) colonial, (ii) post-independence expansion of coverage with basic nursing skills, (iii) professional and academic differentiation of the profession with strategic guidance of the national health workforce plan of 1997-2007, and (iv) a recent expansion of tertiary education training driven by the private for-profit sector.The challenges for nurse education in Angola are similar to those faced by other sub-Saharan African countries. These challenges need to be understood and addressed within a broad health labor market framework, in order to ensure cultural relevance, responsiveness of the cadres trained to the population's and users' needs, fitness to employment opportunities in both public and private sectors and balanced distribution of future graduates between urban and rural and different levels of care.